Financial derivatives in international business – the case of Sweden. (4th August 2014) - Rafferty, Michael
The paper provides an introduction to recent developments in derivatives markets and an overview of emerging research on the implications of derivatives for international business. The influence of derivatives transactions is becoming pervasive in national and international finance markets, and there is a need to understand derivatives as more than just minor instruments for hedging and speculation. The paper also provides data on derivatives markets in Sweden as a case study. Sweden is interesting as a representative of a small open economy which is coming to rely heavily on derivatives as ways that national and international processes are being integrated and commensurated.